Navigating Competency Gaps in ASEAN's Renewable Energy Sector for Economic Growth - Diah Apriliani (Trasearch (Training, Research and Academy Society, 2025)
Background: ASEAN’s transition to renewable energy is hindered by significant competency gaps, with variations in technical and managerial expertise across member states. These gaps present challenges in harnessing the region's renewable energy potential and meeting future energy demands. This study aims to identify these competency gaps and propose strategies to bridge them, ensuring sustainable economic growth. Methods: A mixed-methods approach was employed, beginning with a survey of renewable energy professionals across ASEAN countries to quantify competency levels and skill deficiencies. In-depth interviews with policymakers, industry leaders, and educational representatives provided qualitative insights. Data were analysed using statistical and thematic analysis to identify regional trends and inform recommendations. Results: The study identified significant disparities in competency levels, with advanced nations like Singapore and Malaysia leading in renewable energy expertise, while emerging economies face substantial gaps in areas like energy storage, grid integration, and energy efficiency. The lack of integration between education and industry needs was a key challenge. Conclusions: Addressing the competency gaps is crucial for ASEAN’s renewable energy goals. Strengthening education and training, along with regional coordination, will ensure the development of a skilled workforce capable of driving the energy transition. Implications: The findings highlight the need for policy interventions, such as targeted education programmes and certification schemes, and greater public-private sector collaboration to foster a competent workforce. Limitations: The study's reliance on surveys and interviews may not fully capture the competency needs across all ASEAN countries. Future research should expand the scope and evaluate the effectiveness of training initiatives.